2011
DOI: 10.1364/oe.19.017357
|View full text |Cite
|
Sign up to set email alerts
|

Duration of ultrashort pulses in the presence of spatio-temporal coupling

Abstract: We report on a simple method allowing one to decompose the duration of arbitrary ultrashort light pulses, potentially distorted by space-time coupling, into four elementary durations. Such a decomposition shows that, in linear optics, a spatio-temporal pulse can be stretched with respect to its Fourier limit by only three independent phenomena: nonlinear frequency dependence of the spectral phase over the whole spatial extent of the pulse, spectral amplitude inhomogeneities in space, and spectral phase inhomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Up to now broadbandwidth aperiodic CrSc multilayer mirrors have been investigated only theoretically for the 'water window' [14,15] or have been realized at grazing angles for the keV range [16]. Previous experiments have shown that aperiodic multilayer mirrors can control the attosecond pulse dispersion around 100 eV [5,6,17] being used for resonant excitation of distinct atomic core states [18]. Extending this control, into the 'water window' spectral range, requires multilayer optics of sub-angstrom layer precision as their spectral amplitude and phase are extremely sensitive to even the smallest thickness errors of only a fraction of the nominal layer thickness [19] being typically around 1 nm [20].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now broadbandwidth aperiodic CrSc multilayer mirrors have been investigated only theoretically for the 'water window' [14,15] or have been realized at grazing angles for the keV range [16]. Previous experiments have shown that aperiodic multilayer mirrors can control the attosecond pulse dispersion around 100 eV [5,6,17] being used for resonant excitation of distinct atomic core states [18]. Extending this control, into the 'water window' spectral range, requires multilayer optics of sub-angstrom layer precision as their spectral amplitude and phase are extremely sensitive to even the smallest thickness errors of only a fraction of the nominal layer thickness [19] being typically around 1 nm [20].…”
Section: Introductionmentioning
confidence: 99%
“…This requires that the same focusing optics is used in both probe and pump arms. Imperfect focusing of the attosecond light may induce a spreading of the radiation both in space and in time due to optical aberrations [52][53][54], leading to distortions of the corresponding RABBIT traces. In the following, we do not consider such effects.…”
Section: (A) Spatial Variations Of the Rabbit Phasementioning
confidence: 99%
“…This requires that the same focusing optics is used in both probe and pump arms. Note that imperfect focusing of the attosecond light may induce a spreading of the radiation both in space and in time due to optical aberrations [42,43,44], leading to distorsions of the corresponding RABBIT traces. In the following, we do not consider such effects.…”
Section: Spatial Variations Of the Rabbitt Phasementioning
confidence: 99%